The conflict in the nurse managing exercise in hospital context - preview note. - Soeli Teresinha Guerra; Adelina Giacomelli Prochnow (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This work is the result of a masters dissertation project developed in Post-Graduation Program in Nursing from the Federal University of Santa Maria (UFSM). It has the objective to analyze the conception of conflict in nurses' management exercise in hospital context, as well as to infer the strategies used by them to solve such conflicts. Based on it, one aimed to attempt to the variation assumed by this phenomenon in the range of nurse management exercise in the universe of a hospital type health organization. The semi-structured interview and the focal group, with the identification of the participants, will be used as the collection instruments according to the Resolution 196/96. Based on data recurrence, that will be interpreted using the content analysis technique, one intend to discuss how the conflict has been managed by the nurses and what is the understanding they have about this phenomenon which directly affects their actions even when they deny it.